Simultaneity of the anthropometric markers of adiposity and chronic diseases in women - Silva de Paulo, T. Reis; Ribeiro Dos Santos, V. [UNESP]; Conterato Gomes, I. [UNESP]; Destro Christofaro, D. G.; Fernandes, R. A. [UNESP]; Forte Freitas, I. [UNESP]; Sindra Virtuoso, J. (My University, 2013)
Aim. The aim of this paper was to investigate the relationship between the accumulation of different anthropometric indicators and the prevalence of some chronic diseases in women over 40 years of age. Methods. The sample was comprised of 562 women between 40 and 95 years of age (64.5 ± 11.4) attended by the research projects were carried out in two cities in southeastern Brazil. Anthropometric measurements were taken: weight, height, waist circumference, hip circumference, and the values of BMI and WHR were later calculated. The referenced morbidity questionnaire was also applied, based on the Standard Health Questionnaire (SHQ), which analyzes the presence of degenerative chronic diseases in the adult population. For the statistical treatment, the chi-square and binary logistic regression tests were performed, with significance set at 5%. Results. The relationship between three changes in the anthropometric indicators and the greater incidence of diseases continued significant for hypertension (OR=3.77 [95% CI: 2.14-6.65], =P=0.001), and for endocrine and metabolic diseases (OR=2.59 [95%: 1:47 to 4:32], =P=0.001), regardless of the effects of age and physical activities. Conclusion. The simultaneity of body fat indicators is more strongly associated with the prevalence of some chronic diseases (hypertension, endocrine, and metabolic), relative to the individualized use of anthropometric indicators.
Keywords: Adiposity; Anthropometry; Body mass index; Chronic disease; abdominal obesity; adult; age distribution; aged; anthropometric parameters; body fat; body height; body mass; body weight; Brazil; cardiovascular disease; chronic disease; degenerative disease; disease association; endocrine disease; female; hip circumference; human; hypertension; major clinical study; metabolic disorder; morbidity; obesity; osteoarthropathy; physical activity; prevalence; questionnaire; waist circumference